El proceso penal ante la inseguridad sentida. Límites y elementos para una propuesta dogmática procesal penal restrictiva del peligrosismo - Zuluaga Taborda, John (2025)
This article problematizes the way in which criminal investigation has become functional to the strategies for managing the felt insecurity that is expressed in sensations of risk, danger, uncertainty or fear. In the understanding that the penal system validates security expectations that take shape especially in police and judicial rationalities, the aim is to establish how this security orientation is expressed in the processes of construction of criminal suspicions, i.e., how it influences the judgments of probability of authorship and participation that enable many investigative measures, restrictive of fundamental rights. In order to understand this correlation, an approach is made to the way in which security policies determine criminal discourse and praxis. From this, we try to suggest some standards for the definition of inculpatory probabilities that could contribute to the restriction of the dangerous justifications of many investigative practices. As a result, limits and elements for a restrictive criminal procedural dogmatic proposal of dangerousness are offered.